2001
DOI: 10.1051/0004-6361:20000201
|View full text |Cite
|
Sign up to set email alerts
|

The "rotation-activity connection": Its extension to photospheric activity diagnostics

Abstract: Abstract. In this paper we present the results of a different approach in the study of the so-called rotation-activity connection, which is a well established correlation between rotation and magnetic activity at chromospheric and outer atmospheric levels. The present study concerns the photospheric level and was carried out by using V -band photometric light curve amplitudes as indicators of starspot coverage and of magnetic activity. A high degree of correlation between the envelope of maximum V -band light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 53 publications
5
87
0
Order By: Relevance
“…As discussed in Paper I, there is some marginal (yet) evidence of some other age-dependent quantity, in addition to mass and rotation, that controls the level of (photospheric at least) activity and makes older stars less active than younger stars (see also Messina et al 2010). A similar suspect has already been raised by Messina et al (2001), who found evidence that, for a fixed mass and rotation period, the level of starspot activity increases (or alternatively the gross surface distribution of spots changes) from the zero-age main sequence up to the Pleiades age (∼120 Myr) and then it decreases with age. With the data of M 11 G stars in hand, we can state that up to the M 11 age the level of activity remains at highest levels.…”
Section: Photospheric Activitymentioning
confidence: 68%
See 1 more Smart Citation
“…As discussed in Paper I, there is some marginal (yet) evidence of some other age-dependent quantity, in addition to mass and rotation, that controls the level of (photospheric at least) activity and makes older stars less active than younger stars (see also Messina et al 2010). A similar suspect has already been raised by Messina et al (2001), who found evidence that, for a fixed mass and rotation period, the level of starspot activity increases (or alternatively the gross surface distribution of spots changes) from the zero-age main sequence up to the Pleiades age (∼120 Myr) and then it decreases with age. With the data of M 11 G stars in hand, we can state that up to the M 11 age the level of activity remains at highest levels.…”
Section: Photospheric Activitymentioning
confidence: 68%
“…This is consistent with the expected dependence on rotation rate of the efficiency of magnetic field generation and intensification by an αΩ dynamo. The solid line represents the fit to the upper envelope of the light curve amplitude distribution of slowly rotating Pleiades G stars (110 Myr) taken from Messina et al (2001Messina et al ( , 2003. With the data at our disposal, we do not see any significant difference between the 110-Myr and the 230-Myr distribution upper envelopes.…”
Section: Photospheric Activitymentioning
confidence: 81%
“…The amplitude of the light curve provides a lower limit on the amount of magnetic fields asymmetrically distributed along the stellar longitude, which is in turn proportional to the total magnetic field filling factor. As shown by Messina et al (2001, the upper bound of the light curve amplitude distribution is observed to decrease with increasing rotation period, when the dynamo becomes less efficient. In Fig.…”
Section: Rotation-photospheric Activity Connectionmentioning
confidence: 89%
“…Column 14 contains important notes: spectroscopic binaries radial velocities standards, and stars in chromospherically active binary systems are identified in this column. Tables 9 to 13 Baliunas et al (1996); (3) Duncan et al (1991) calculated using equations in Noyes et al (1984); (4) Gray et al (2003); (5) Gray et al (2006); (6) Hall et al (2007); (7) Henry et al (1996); (8) Jenkins et al (2006); (9) Saffe et al (2005); (10) Wright et al (2004); (11) estimated form ROSAT-data using equation A1 in Mamajek & Hillenbrand (2008); (12) Noyes et al (1984); (13) Saar & Osten (1997); (14) Messina et al (2001).…”
Section: Appendix A: Tablesmentioning
confidence: 99%